2010
DOI: 10.1099/ijs.0.009514-0
|View full text |Cite
|
Sign up to set email alerts
|

Amplified fragment length polymorphism and multilocus sequence analysis-based genotypic relatedness among pathogenic variants of Xanthomonas citri pv. citri and Xanthomonas campestris pv. bilvae

Abstract: INTRODUCTIONThe classification of some phytopathogenic bacterial species was initially based on host specialization, although this was evidently not sound taxonomically (Dowson, 1939;Stolp et al., 1965). Nevertheless, plant pathologists and phytosanitary policy regulators required names for plant-pathogenic bacteria that clearly reflected their pathogenic ability. This led to the development of the pathovar classification at an infrasubspecific level (Dye et al., 1980). Furthermore, strains with differential h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 68 publications
2
61
0
1
Order By: Relevance
“…The taxonomic and phylogenetic status of the genus Xanthomonas has been subjected to considerable debate, with various genuswide and subspecific reclassifications proposed (5,6,58,59). This can be attributed to the limited DNA markers used in traditional approaches of classification (5-8).…”
Section: Discussionmentioning
confidence: 99%
“…The taxonomic and phylogenetic status of the genus Xanthomonas has been subjected to considerable debate, with various genuswide and subspecific reclassifications proposed (5,6,58,59). This can be attributed to the limited DNA markers used in traditional approaches of classification (5-8).…”
Section: Discussionmentioning
confidence: 99%
“…allii if a false-positive signal is suspected. If necessary, AFLP or multilocus sequence analysis methods can also be used to confirm the diagnosis after isolation of the bacteria (8).…”
Section: Discussionmentioning
confidence: 99%
“…All strains of X. citri pv. citri were previously genotyped by AFLP using four selective primer pairs or were AFLP-typed during the present study, as reported earlier [29], [39]. We used AFLP as our genotyping reference method.…”
Section: Methodsmentioning
confidence: 99%
“…citri has been examined at nine housekeeping genes [38], [39]. The currently targeted housekeeping genes display extremely low polymorphism and do not provide sufficient resolution of X. citri pv.…”
Section: Introductionmentioning
confidence: 99%